Mongolian Loanwords in the Figurative Words of the Yakut Language (Illustrated by Verbs of Body Parts) - Shamaeva, Anastasia Egorovna; Prokopieva, Svetlana Mitrofanovna (Journal of History Culture and Art Research, 2018)
The Yakut language is a Turkic language of the Uyghur group. It has a special place among the Turkic languages due to its archaic nature and unique characteristics of vocabulary and grammar. It is distinct from related Turkic languages by abundance of Mongolian parallels. Figurative verbs take a special place among Mongolian loanwords in Yakut due to their quantitative prevalence and specific nature as compared to other sections of Yakut vocabulary. It is of great importance to study Yakut-Mongolian contacts further to reveal the historical development of the Yakut language. The purpose of this study is to find common and specific semantic characteristics of Yakut figurative verbs and their Mongolian parallels. It is the first study to undertake this comparison. Verbs with figurative meaning borrowed from Mongolian are studied by example of verbs denoting parts of human body in comparison to their Mongolian parallels. Common and specific features are revealed in terms of semantics. 20 percent of linguistic units fully coincide. Concretization of word semantics in Yakut shows a high rate. It has also been revealed that Mongolian loanwords with figurative meaning are involved in description of practically all parts of body, thus forming a separate microsystem of somatisms in the Yakut verbal system.